2023
DOI: 10.1007/s10072-023-06903-9
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for cognitive impairment: a telephone survey of patients’ experiences with neurological video consultation

Abstract: Objective This study aimed to evaluate the experience with telemedicine in patients with cognitive impairments and their caregivers. Methods We conducted a survey-based study of patients who completed neurological consultation via video link between January and April 2022. Results A total of 62 eligible neurological video consultations were conducted for the following categories of patients: Alzheimer’s disease (33.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Evidence reveal escalating pressures on families and caregivers, both emotionally and financially, alongside substantial financial strains on the entire healthcare system (10). Hence, telemedicine services represent an innovative solution that lessens the burden on patients' support networks, is more environmentally friendly, and incurs reduced costs compared to in-person appointments (11)(12)(13). While further investigations are necessary to gauge the environmental impact and social costs, telemedicine has been reported as a feasible approach to assist individuals with dementia stay connected to their service providers amid the pandemic (14).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence reveal escalating pressures on families and caregivers, both emotionally and financially, alongside substantial financial strains on the entire healthcare system (10). Hence, telemedicine services represent an innovative solution that lessens the burden on patients' support networks, is more environmentally friendly, and incurs reduced costs compared to in-person appointments (11)(12)(13). While further investigations are necessary to gauge the environmental impact and social costs, telemedicine has been reported as a feasible approach to assist individuals with dementia stay connected to their service providers amid the pandemic (14).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have indicated positive perceptions toward the use of telemedicine among patients with dementia and their caregivers [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], as well as among patients with Parkinson’s disease [ 7 ]. A recent scoping review aiming to describe the effectiveness and user experience of using telemedicine services for individuals with dementia and their caregivers during the COVID-19 pandemic demonstrated that overall, participants perceive this mode of care delivery positively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%